2021
DOI: 10.1111/bcp.15160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of clinical decision support systems for medication review: A scoping review

Abstract: The aim of this scoping review is to summarize approaches and outcomes of clinical validation studies of clinical decision support systems (CDSSs) to support (part of) a medication review. A literature search was conducted in Embase and Medline. In total, 30 articles validating a CDSS were ultimately included. Most of the studies focused on detection of adverse drug events, potentially inappropriate medications and drug-related problems. We categorized the included articles in three groups: studies subjectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The overall sensitivity of 88.3% aligns with the recommendations that a CDSS should maximise specificity while sensitivity is kept above 75% [ 35 ]. In a scoping review, the clinical validation of several CDSSs for drug-related problems revealed a sensitivity of 28%–85% and a specificity of 42–75% [ 36 ], though these were not studies of CDSS for TW management. A general acceptance rate above 60% is suggested for action-oriented interventions [ 37 ]; our TW algorithm compliance rate was 77.7%, which compares favourably with this standard and with the acceptance rates reported for primary care TW CDSSs (30–82%) [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall sensitivity of 88.3% aligns with the recommendations that a CDSS should maximise specificity while sensitivity is kept above 75% [ 35 ]. In a scoping review, the clinical validation of several CDSSs for drug-related problems revealed a sensitivity of 28%–85% and a specificity of 42–75% [ 36 ], though these were not studies of CDSS for TW management. A general acceptance rate above 60% is suggested for action-oriented interventions [ 37 ]; our TW algorithm compliance rate was 77.7%, which compares favourably with this standard and with the acceptance rates reported for primary care TW CDSSs (30–82%) [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first scoping review which attempts to identify the characteristics of studies in which different types of CDSSs were used to effectively support clinical decision in different settings. Previous scoping reviews have focused on CDSSs for medication review, rare-disease diagnosis, non-knowledge-based clinical decision support tools and on CDSSs to be used in nursing homes 6 19–21…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, real-world patients are complex, with multiple conditions and medications. Current tools however lack intelligent algorithms to account for multiple complex interactions in a patient, for example, different drug–food and drug–gene interactions (Finkelstein et al, 2016 ; Mehta et al, 2021 ; Westerbeek et al, 2021 ; Damoiseaux-Volman et al, 2022 ; Mouazer et al, 2022 ). Additionally, an important consideration in precision medicine is distinguishing between theoretical and clinically relevant drug interactions for a particular patient, which is another limitation.…”
Section: Current Approach To Precision Medicine In Polypharmacymentioning
confidence: 99%